Saccharification of thermochemically pretreated cellulosic biomass using native and engineered cellulosomal enzyme systems. Issue 6 (21st October 2016) - Chundawat, Shishir P. S.; Paavola, Chad D.; Raman, Babu; Nouailler, Matthieu; Chan, Suzanne L.; Mielenz, Jonathan R.; Receveur-Brechot, Veronique; Trent, Jonathan D.; Dale, Bruce E.
Abstract : Tethering hydrolytic enzymes ( e.g., cellulases) to protein scaffolds enhances biomass saccharification to sugars. Abstract : Consolidated bioprocessing (CBP) of pretreated lignocellulosic biomass using microbes like Clostridium thermocellum allows simultaneous polysaccharide saccharification and sugar fermentation to produce fuels or chemicals using a one-pot process. C. thermocellum is a thermophilic bacterium that deconstructs biomass using large multi-enzyme complexes called cellulosomes. Characterization of cellulosomal enzymes tethered to native or engineered scaffoldin proteins has revealed that enzyme complexation is critical to the bacterium's cellulolytic ability. However, we have a limited understanding of the impact of enzyme complexation on the saccharification efficiency of various forms of industrially relevant pretreated biomass substrates. Here, we compared the hydrolytic activity of the most abundant cellulosomal enzymes from C. thermocellum and investigate the importance of enzyme complexation using a model engineered protein scaffold (called 'rosettasome'). The hydrolytic performance of non-complexed enzymes, enzyme-rosettasome (or rosettazyme) complexes, and cellulosomes was tested on distinct cellulose allomorphs formed during biomass pretreatment. The scaffold-immobilized enzymes always gave higher activity than free enzymes. However, cellulosomes exhibited higher activity than rosettazyme complexes. This was likely due to the greater flexibility of the native versus engineered scaffold, as deciphered using small angle X-ray scattering. Surprisingly, scaffold-tethered enzymes also gave comparable activity on all the cellulose allomorphs tested, which is unlike the preferential activity of non-complexed cellulases seen for certain allomorph forms. Tethered enzyme complexes also gave lower saccharification yields on industrially relevant lignin-rich switchgrass than cellulose alone. In summary, we find that the type of pretreatment can significantly impact the saccharification efficiency of cellulosomal enzymes for various CBP scenarios.